Spirit week showdown - Allen, Crystal (Allen, Crystal. Magnificent Mya Tibbs, 2016)
Nine-year-old Mya is excited about participating in School Spirit Week, even making a pinky promise with her best friend Naomi to be her partner, but when she accidentally gets paired with the biggest bully in school, Mean Connie, Naomi is mad at Maya for breaking her promise, so she must learn to work with Mean Connie and try and get her friend back.